2019
DOI: 10.1051/e3sconf/201911001048
|View full text |Cite
|
Sign up to set email alerts
|

Study of polymer adhesion to steel

Abstract: Tests on the dependence of glues shear strength on: gluing temperature, keeping time before testing, cooling environment, surface roughness, surface conditions, temperature and time of drying on air and in drying oven were carried out to select proper thermoplastics to use as glues for connection of steel elements together. The highest shear strength was showed by the following materials: desmopan 150, antifriction polyamide PA 610-L-DM, impact-resistant glass-filled polyamide. Given results allow significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As product users pay more attention to the adhesiveness and corrosion resistance of plating [20][21][22][23], the flat plates should be corrosion resistant and the corrosion resistance after bending is required. Therefore, during the trial production of hot-rolled aluminum-zinc plating products, the project team samples the hot-dip aluminum-zinc plating products and tests the plating structure, bending forming performance and corrosion resistance.…”
Section: Product Quality In Kindmentioning
confidence: 99%
“…As product users pay more attention to the adhesiveness and corrosion resistance of plating [20][21][22][23], the flat plates should be corrosion resistant and the corrosion resistance after bending is required. Therefore, during the trial production of hot-rolled aluminum-zinc plating products, the project team samples the hot-dip aluminum-zinc plating products and tests the plating structure, bending forming performance and corrosion resistance.…”
Section: Product Quality In Kindmentioning
confidence: 99%
“…According to the technical requirements of users and the practical production experience of hot-rolled galvanized products, the chemical compositions, mechanical properties and size accuracy of the products are mainly determined by the raw steel coils, and the technical difficulties of such projects lie in how to keep the adhesion of the coating and avoid defects such as skip plating and exposed steel substrate, so as to ensure surface quality. These defects with hot-rolled galvalume products can lead to quality degradation, Artiukh et al [14] and Cole [15] found the main causes of these defects via analysis and verification and proposed good solutions. In terms of another type of surface defects, bright pitting, for users in the construction industry, although it might not cause serious problems such as quality decline, it can affect the appearance of the products since the color of the defect area is different from the surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration of the protective zinc coating can cause the development of corrosion of the base metal [4][5][6][7]. To protect the zinc coating itself and increase the service life of metal products, duplex-technologies, associated with the application of an additional polymer (for example, based on polyester) or lacquer and paint coating (lacquering, painting) are widely used [1,3,[8][9][10][11]. Welding and gas cutting of galvanized steel products are not allowed to exclude thermal destruction of the zinc coating.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the life duration of galvanized steel structures, enclosing structures should include measures to prevent the formation of condensate on the surface of metal products. Special attention is paid to the implementation of vapor barrier, waterproofing and thermal insulation, excluding the formation of "cold bridges" [8,10,12]. If stored or transported improperly with moisture accumulating in the space between loose products, it may freeze at the joints or form ice at the dew point in winter, metal swell or delamination.…”
Section: Introductionmentioning
confidence: 99%